1989
DOI: 10.1021/jm00124a024
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and D2 dopaminergic activity of pyrrolidinium, tetrahydrothiophenium, and tetrahydrothiophene analogs of sulpiride

Abstract: All of the existing dopamine receptor models recognize the amine nitrogen of agonist and antagonist drugs as playing a crucial role in receptor interactions. However, there has been some controversy as to which molecular form of the amine, charged or uncharged, is most important in these interactions. We have synthesized and examined the biological activity of permanently charged and permanently uncharged analogues of the dopaminergic antagonist, sulpiride. Sulpiride and the permanently charged pyrrolidinium (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Because antipsychotic drugs are thought to bind to D2 receptors in part via their positively charged amine moieties (Harrold et al ., 1989), antipsychotics should be weak bases . Indeed, all have pK values in the range of 7 .0-9.5 (see references in Table 1), indicating that some antipsychotic molecules will be neutral at physiological pH [or zwitterions forming an internal salt, as is the case for raclopride and will partition across membranes .…”
Section: Discussionmentioning
confidence: 99%
“…Because antipsychotic drugs are thought to bind to D2 receptors in part via their positively charged amine moieties (Harrold et al ., 1989), antipsychotics should be weak bases . Indeed, all have pK values in the range of 7 .0-9.5 (see references in Table 1), indicating that some antipsychotic molecules will be neutral at physiological pH [or zwitterions forming an internal salt, as is the case for raclopride and will partition across membranes .…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, work by Xu and coworkers demonstrated that the chiral tetrahydrothiophene compounds 44-46, which exhibited D2 dopaminergic activity and anti-HIV activity as well, [29] could be synthesized by an efficient method via a bifunctional squaramide C2-catalyzed domino sulfa-Michael/aldol reaction between 1,4-Dithiane-2,5-diol 43 and chalcones in high yields (71-91%) and excellent stereoselectivities (8: 1-20: 1 dr and 84-97% ee values) (Scheme 17). [30,31] Cyclobutane derivatives are significant drug intermediates with higher stability than cyclopropane.…”
Section: Enantioselective Synthesis Of Other Heteroatomcontaining Commentioning
confidence: 99%
“…[20]. The final product was prepared by a modified method applied for the preparation of n-butyl isothiocyanate [19]: A mixture of 2-thiolanylmethylamine (1.23 g, 10.5 mmol), triethylamine (1 mL, 0.73 g, 7.2 mmol) and 2 mL of dioxane was chilled to -10°C and treated with Scheme 1 Thiourea ligands used in this study carbon disulfide (0.5 mL, 0.63 g, 8.3 mmol).…”
Section: Preparation Of L2mentioning
confidence: 99%